Pemanfaatan Data Sensus Pertanian untuk Mendukung Program Land Reform: Kasus Kabupaten Blitar dan Luwu Utara - Mohamad Shohibuddin; Anisa Dwi Utami; Dina Nurdinawati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2021)
Abstract: The success of land reform depends, among others, on complete and accurate data on land tenure. Such data are still lacking since land registration has not been completed yet, while the completed ones are difficult to access. Actually, agriculture census data contain some information concerning farm landholding, although the last concept refers to “effective landholding” rather than “formal landholding” (legal ownership) as frequently used in land reform program. Using literary study, this article aims to analyse the 2013 Agricultural Census with special focus on Blitar in East Java and Luwu Utara in South Sulawesi to represents two types of ecosystems in Geertz’s conception, namely “Inner Indonesia” and “Outer Indonesia” respectively. The analysis resulted in detailed descriptions on the distribution of farm households, farmland use, and inequality of landholding which can be traced until the village level. For preparing land reform, it is important to combine this information with existed data on land ownership and to use it as a basis for further field-based inventories on farmland holding, ownership, use and utilization. This article concludes that the benefit of agricultural census data should be optimized. Some policy recommendations are also provided, emphasizing the urgency for more contextual way to implement land reform. Keywords: Agricultural Census, Land Reform, Farm Household, Inequality of Landholding, Blitar, Luwu Utara Intisari: Keberhasilan program land reform bergantung antara lain pada data penguasaan tanah yang lengkap dan akurat. Data semacam ini masih belum memadai karena pendaftaran tanah di seluruh Indonesia belum tuntas, sementara data yang sudah tersedia sulit diakses. Sebenarnya, Sensus Pertanian mengandung banyak informasi mengenai penguasaan lahan pertanian, sekalipun konsep “penguasaan” ini mengacu pada “penguasaan efektif” dan bukan “penguasaan formal” (alias kepemilikan legal) yang sering dimanfaatkan dalam program land reform. Menggunakan studi pustaka, artikel ini bertujuan untuk menganalisis data mentah Sensus Pertanian 2013 dengan fokus di Kabupaten Blitar, Jawa Timur dan Luwu Utara, Sulawesi Selatan. Dua kabupaten ini dipilih secara purposive untuk mewakili dua tipe ekosistem yang berbeda dalam konsepsi Geertz, yakni berturut-turut “Indonesia Dalam” dan “Indonesia Luar”. Hasil analisis menyajikan deskripsi detail mengenai sebaran rumah tangga petani, penggunaan lahan pertanian, dan ketimpangan penguasaan lahan yang bisa ditelusuri hingga ke level desa. Untuk perencanaan land reform, sangat penting untuk memadukan informasi ini dengan data kepemilikan tanah yang ada dan menjadikannya sebagai pijakan bagi inventarisasi Penguasaan, Pemilikan, Penggunaan dan Pemanfaatan Tanah di lapangan. Artikel ini menyimpulkan bahwa manfaat data Sensus Pertanian perlu lebih dioptimalkan. Beberapa rekomendasi kebijakan juga disajikan yang menekankan urgensi pelaksanaan land reform secara lebih kontekstual. Kata Kunci: Sensus Pertanian, Land Reform, Rumah Tangga Petani, Ketimpangan Penguasaan Lahan, Blitar, Luwu Utara